Students’ Views On Using Collaborative Strategic Reading (CSR) To Develop Arabic Composition Writing Skills - Azman, Yusra; Bin Chik, Abdul Rahman (Ijaz Arabi Journal of Arabic Learning, 2024)
Previous studies have indicated decreased students' proficiency in Arabic composition writing. A survey showed that 63.4% of students received a "fragile" score on an Arabic composition test. Numerous factors contribute to this deterioration, such as a limited vocabulary, ineffective reading skills, and a poor ability to organize thoughts. Gaining proficiency in strategic reading is essential for enhancing writing skills. Thus, this study aims to investigate how students perceive the use of Collaborative Strategic Reading to develop Arabic composition writing skills.‎ This quantitative study relies on a questionnaire for data collection, with a sample size of 25 fourth-year secondary school students from Sekolah Agama Menengah Sungai Merab Luar. According to the study, students feel optimistic about utilizing this reading strategy in terms of interest, motivation, and vocabulary expansion. Additionally, the strategy helped students improve their Arabic composition writing skills by assisting them in selecting relevant topics and writing in an appropriate Arabic style.